2010
DOI: 10.1182/blood-2010-06-291906
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of thrombin generation test for dose monitoring of bypassing therapy in hemophilia patients with inhibitors undergoing elective surgery

Abstract: Clinical response to bypassing agents (BPAs) may vary between patients. Surgery is a particular situation, requiring effective hemostasis during the procedure and for several days postoperatively to obtain satisfactory wound healing. However, the optimal dose of BPA in different surgical situations has not been clearly established. We report here a prospective assessment of thrombin generation test (TGT) in monitoring the effectiveness of BPA during 10 elective invasive procedures performed in 6 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(165 citation statements)
references
References 12 publications
10
153
1
1
Order By: Relevance
“…The logical conclusion is that thrombin generation in these patients is a more sensitive parameter than factor VIII. Other observations showed that thrombin generation, which is low in patients with hemophilia, increased substantially after infusion of bypassing agents (40 ). The above observations paved the way to investigate TGA as a reliable laboratory tool to monitor hemophiliacs during replacement therapy.…”
Section: Application Of Tga To Manage Patients With Hemorrhagic Coagumentioning
confidence: 99%
“…The logical conclusion is that thrombin generation in these patients is a more sensitive parameter than factor VIII. Other observations showed that thrombin generation, which is low in patients with hemophilia, increased substantially after infusion of bypassing agents (40 ). The above observations paved the way to investigate TGA as a reliable laboratory tool to monitor hemophiliacs during replacement therapy.…”
Section: Application Of Tga To Manage Patients With Hemorrhagic Coagumentioning
confidence: 99%
“…Data have been published with the CAT method, consistent with a potentially high added value in clinical practice, in settings such as diagnosis and management of bleeding disorders [6][7][8], detection of hypercoagulability [9,10], characterization/monitoring of anticoagulant drugs including non-vitamin K antagonist oral anticoagulants [11,12] or even in acquired complex coagulation disorders [13]. Most of the data come from single-centre studies and must be confirmed in prospective, large, multicentre studies.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 There is also a relationship between bleeding and failure to normalize ETP in hemophilia patients with inhibitors treated with inhibitor bypass agents at the time of surgery. 27 We therefore studied thrombin generation in patients with discrepant factor FVIII:C assays and compared it to that in patients with non-discrepant assays and normal subjects given suggestions in the literature that two-stage assays and chromogenic assays may correlate than one-stage assays with the clinical phenotype. 4 Gilmore et al reported on the effect of three mutations linked to lower two-stage discrepancy (p.Arg550His/Cys and p.Arg717Trp) on CAT, demonstrating impaired thrombin generation in this group similar to non-discrepant patients with the mean ETP being 58-67% of normal and peak thrombin generation being 27-30% of normal.…”
Section: Calibrated Automated Thrombographymentioning
confidence: 99%